Evaluation of climate disaster resilience index in Yan District's local plan in Kedah, Malaysia - Asmawi, Zainora; Dewan, Ashraf; Ab Rahman, Syakir Amir; Abdul Aziz, Maimunah (Malaysia Institute of Planners, 2025)
Assessing the resilience of urban areas is crucial for effective disaster planning and management. The Climate Disaster Resilience Index (CDRI) is a widely recognized tool used globally to evaluate the current and future risks faced by cities and guide policy development. This research focuses on the application of the CDRI in Yan, Kedah to assess the district's resilience in the context of Local Plan preparation. A comprehensive evaluation was conducted across various components, including physical, social, economic, institutional, and environmental aspects. A total of 97 respondents from agencies and communities participated in the survey through online and face-to-face methods. The physical component in Yan District exhibited the highest resilience to disasters, with all aspects receiving resilience scores ranging from 3 (moderately satisfactory) to 4 (satisfactory). However, the economic component had the lowest CDRI score of 2.99 compared to the other components, indicating a need to focus on economic development to enhance disaster resilience in the district. The overall CDRI performance of the district suggests that local stakeholders are prepared to effectively manage disasters. The findings from the CDRI assessment can guide future planning efforts to promote more resilient development in Yan District